The Psychological Approach in Islamic Study - M. Iqbal , Azmi Al-Latif (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2023)
The purpose of this study is to explain how psychology may be used to the study of Islam. Documentary studies found in scholarly journals and books form the basis of our qualitative research methodology. The findings of this research 1) The psychological symptoms associated with religion, such as piety, good deeds, and honesty, as described by religious teachings, such as the nature of faith and devotion to Allah. As a tool for spiritual development according to one's age, this psychology might reveal how deeply one has internalized and acted upon one's religious beliefs. Knowing the impact of prayer, fasting, zakat, hajj, and other acts of worship on a Muslim's life is an important part of studying Islam, and the psychological approach in Islamic Studies is helpful for this purpose.